A Concise Review of Gold Nanoparticles-Based Photo-Responsive Liposomes for Controlled Drug Delivery - Mathiyazhakan, Malathi; Wiraja, Christian; Xu, Chenjie (Nano-Micro Letters, 2017)
The focus of drug delivery is shifting toward smart drug carriers that release the cargo in response to a change in the microenvironment due to an internal or external trigger. As the most clinically successful nanosystem, liposomes naturally come under the spotlight of this trend. This review summarizes the latest development about the design and construction of photo-responsive liposomes with gold nanoparticles for the controlled drug release. Alongside, we overview the mechanism involved in this process and the representative applications. Highlights: 1 Photo-responsive liposomes are powerful carriers for topical and transdermal drug delivery to superficial tissues like skin, eyes, and mucous membranes. 2 Photo-responsive liposomes can be built with gold nanoparticles, which allow the use of near-infrared lights as the light source for deep tissue penetration and low phototoxicity. 3 This review summarizes the latest development and scientific understanding of this complex in delivering drugs for tuning cell signaling pathway and treating cancer.